The Family System in the Social and Cultural Structure of Islamic Society in Indonesia - Putra Pandu Dinata Nurdiansyah; Ria Anjani; M. Aunul Hakim (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2025)
Kinship or family systems include marriage and descent relationships, where a person is considered a relative if they are related by blood, such as siblings. Kinship systems shape the social structure of society and depend heavily on it. This research aims to understand and analyze the function of the kinship system in shaping and influencing the social and cultural structure of Indonesian society. The study will also identify the problems faced and provide suggestions for the development and reconstruction of the kinship system to ensure fair justice. This research uses library research with a sociological approach. This study concluded that the kinship system plays an important role in the formation and influence of social and cultural dynamics among Indonesian Islamic societies. This study shows that kinship systems, especially those based on Islamic values, strengthen family relationships and preserve cultural values passed down from generation to generation. Nonetheless, the study also found challenges in adjusting traditional values to social change and modernity. It is hoped that sustainable solutions can be found to maintain a balance between Islamic traditions and the needs of modern Indonesian society by understanding the role and complexity of these kinship systems.